Assessment of Bacterial Contamination in Drinking water of Schools of Tokha Municipality, Kathmandu - Shrestha, Ganga; Shrestha, Mohan Bikram; Byanju, Rejina Maskey (Journal of Environment Sciences, 2022)
Assessment of drinking water quality is being crucial especially in school institutions since children spend most of the time in school premises. The aim of this study was to assess bacterial contamination of the selected schools of Tokha Municipality. Total of 17 water samples from Ward 1, 2 and 3 were sampled and membrane filtration (MF) technique was used to analyses total coliform and fecal coliform incubated for 37 °C and 44 °C respectively. Multiple drinking water sources were found in the study area such as natural springs, piped-line system, bottled water and private wells. Almost all of the water samples exceeded WHO guideline and National Drinking Water Standards which implied none of the water samples are safe for drinking. Very few schools were found to adopt purification measures while other used to supply directly. Water samples of school were even not tested once in many schools for microbial analysis. Therefore, school management need to be responsible in coming days to ensure safe drinking water not just for children, for the wellbeing of the society and Nation.